2006
DOI: 10.4269/ajtmh.2006.74.263
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Dengue Type 3 Viruses Associated With the Dengue Outbreak in Dhaka, Bangladesh, in 2000 and 2001

Abstract: Dengue and dengue hemorrhagic fever re-emerged in Bangladesh in 2000 and 2001 and nearly all viruses isolated were dengue type 3. Phylogenetic analyses of the envelope genes of examples of these viruses indicated that they were most closely related to recently emerged dengue type 3 viruses from neighboring Thailand and Myanmar but distinct from those from India and Sri Lanka. Since this strain of dengue virus type 3 had not been associated with unusual patterns of disease in Thailand or Myanmar, it suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Broadcasting of the virus from India to Cambodia was also indicated with a significant BF value. On the other hand, Bangladesh and Myanmar were populated with GII viruses from South-east Asia as suggested earlier (Podder et al, 2006) and also shown from the present phylogeography studies. Further, dispersal of the virus from Sri Lanka to Africa and Central America was also supported by significant values of BF (Table S7A).…”
Section: Discussionsupporting
confidence: 68%
“…Broadcasting of the virus from India to Cambodia was also indicated with a significant BF value. On the other hand, Bangladesh and Myanmar were populated with GII viruses from South-east Asia as suggested earlier (Podder et al, 2006) and also shown from the present phylogeography studies. Further, dispersal of the virus from Sri Lanka to Africa and Central America was also supported by significant values of BF (Table S7A).…”
Section: Discussionsupporting
confidence: 68%
“…Similar studies in India suggest that genotype V of DENV-2 was replaced by genotype IV between 1967 and 1996 (Singh et al, 1999). DENV-3 strains isolated from Bangladesh in 2000 and 2001 were most closely related to recently emerged DENV-3 from neighboring Thailand and Myanmar, but distinct from those isolated in India and Sri Lanka (Podder et al, 2006). DENV-3, subtype III, which apparently originated in the Indian subcontinent, appears to have spread into Africa during the 1980s and from Africa into Latin America during the 1990s.…”
Section: Contributions Of Phylogenetics To the Understanding Of Dementioning
confidence: 86%
“…The first identified epidemic of DF and dengue hemorrhagic fever (DHF) in Bangladesh, took place during the monsoon season of 2000, and resulted in 5,521 officially reported cases with 93 fatalities [17–18]. Based on molecular diagnostic testing of persons with acute disease, all four dengue serotypes have been found in circulation in recent years [19–21]. From 2000–2009, 91.0% of all reported dengue cases were from Dhaka making it the most endemic urban area of the country [22].…”
Section: Introductionmentioning
confidence: 99%